2018
DOI: 10.1111/joop.12215
|View full text |Cite
|
Sign up to set email alerts
|

Personality and expatriate adjustment: A meta‐analysis

Abstract: We used meta‐analysis to advance our understanding of personality traits as antecedents of expatriate adjustment to international assignments and to test expatriate adjustment as a mediator linking the Five‐Factor Model (FFM) of personality to job performance and turnover intentions (k = 43; N = 7,007). Personality accounted for 20% of the variance in expatriate adjustment. Relative weight analyses indicated that extraversion generally accounted for the greatest proportion of predicted variance, although emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 116 publications
(163 reference statements)
7
64
0
3
Order By: Relevance
“…However, because performance dimension scores tend to intercorrelate strongly (due to both substantive and extraneous factors), discriminant validity needed to tease out these differences might not exist in most data (Harari et al ., ; Viswesvaran et al ., ). In addition to narrower performance criteria, the same potential might exist for non‐performance effectiveness criteria that are predicted by personality traits (e.g., expatriate adjustment; Harari, Reaves, Beane, Laginess, & Viswesvaran, ); research comparing global and facet validities across time for such criteria is needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, because performance dimension scores tend to intercorrelate strongly (due to both substantive and extraneous factors), discriminant validity needed to tease out these differences might not exist in most data (Harari et al ., ; Viswesvaran et al ., ). In addition to narrower performance criteria, the same potential might exist for non‐performance effectiveness criteria that are predicted by personality traits (e.g., expatriate adjustment; Harari, Reaves, Beane, Laginess, & Viswesvaran, ); research comparing global and facet validities across time for such criteria is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although we examined the role of sex, there are several other individual differences that may play a role in determining which expatriates benefit most from general and targeted types of support. In light of meta-analytic evidence that extraversion is the most important personality trait in predicting expatriate adjustment (Harari, Reaves, Beane, Laginess, & Viswesvaran, 2018), for example, it could be interesting to examine whether expatriate targeted forms of support (e.g. OCQ) could help to bolster the adjustment and longevity attitudes of introverts who may struggle to form bonds with host country nationals.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…The study revealed that personality is one of the factors that contributed 20% of the variance in expatriate adjustment. In the study by Harari et al [30], cultural adjustment was influenced by the individual"s emotional stability and openness. Wechtler et al [31] found that age facilitates regulation of emotions on general living adjustment and interactional adjustment.…”
Section: The Conceptualization Of Cultural Adjustmentmentioning
confidence: 99%
“…A recent study by Salgado and Bestida [29] revealed that for successful cultural adjustment, expatriates need organizational support, language skills and social skills. Harari et al [30] studied personality traits as antecedents of expatriate adjustment. The study revealed that personality is one of the factors that contributed 20% of the variance in expatriate adjustment.…”
Section: The Conceptualization Of Cultural Adjustmentmentioning
confidence: 99%